LDL-cholesterol lowering with evolocumab, and outcomes according to age and sex in patients in the FOURIER Trial. (5th February 2020) - Sever, Peter; Gouni-Berthold, Ioanna; Keech, Anthony; Giugliano, Robert; Pedersen, Terje R; Im, KyungAh; Wang, Huei; Knusel, Beat; Sabatine, Marc S; O'Donoghue, Michelle L
Abstract: Aims: Some trials have reported diminished efficacy for statins in the elderly, and in women compared with men. We examined the efficacy and safety of evolocumab by patient age and sex in the FOURIER trial, the first major cardiovascular outcome trial of a PCSK9 inhibitor. Methods and results: FOURIER was a randomised, double blind trial, comparing evolocumab with placebo in 27, 564 patients with atherosclerotic cardiovascular disease receiving statin therapy (median follow-up 2.2 years). The primary endpoint was cardiovascular death, myocardial infarction, stroke, hospitalisation for unstable angina or coronary revascularisation. Cox proportional hazards models were used to assess the efficacy of evolocumab versus placebo stratified by quartiles of patient age and by sex. There were small variations in the cardiovascular event rate across the age range (for the primary endpoint, Kaplan–Meier at 3 years 15.6%, >69 years, vs. 15.1%, ≤56 years, P  = 0.45); however, the relative efficacy of evolocumab was consistent regardless of patient age (for the primary endpoint (Q1 hazard ratio, 95% confidence interval) 0.83, 0.72–0.96, Q2 0.88, 0.76–1.01, Q3 0.82, 0.71–0.95, Q4 0.86, 0.74–1.00; P interaction  = 0.91), and the key secondary endpoint (cardiovascular death, myocardial infarction, stroke) (Q1 0.74 (0.61–0.89), Q2 0.83 (0.69–1.00), Q3 0.78 (0.65–0.94), Q4 0.82 (0.69–0.98)); P interaction  = 0.81). Women had a lower primary endpoint rate than men (Kaplan–Meier at 3 years 12.5 vs. 15.3%, respectively, P  < 0.001). Relative risk reductions in the primary endpoint and key secondary endpoint were similar in women (0.81 (0.69–0.95) and 0.74 (0.61–0.90), respectively) compared with men (0.86 (0.80–0.94) and 0.81 (0.73–0.90), respectively), P interaction  = 0.48 and 0.44, respectively. Adverse events were more common in women and with increasing age but, with the exception of injection site reactions, there were no important significant differences reported by those assigned evolocumab versus placebo. Conclusions: The efficacy and safety of evolocumab are similar throughout a broad range of ages and in both men and women.